2008
DOI: 10.1007/s10620-008-0379-7
|View full text |Cite|
|
Sign up to set email alerts
|

Site Specific Delivery of Microencapsulated Fish Oil to the Gastrointestinal Tract of the Rat

Abstract: The aim of this study was to design food grade matrices to deliver microencapsulated fish oil to the large bowel of the rat where the potential exists to retard inflammation and cancer development. Digestion in simulated gastric fluid and intestinal fluid demonstrated that only 4-6% of oil was released from the following dried emulsion formulations: 50% fish oil encapsulated in heated casein-glucose-dried glucose syrup (1:1:1) (Cas-Glu-DGS-50); 25% fish oil in casein-modified resistant starch (Hylon VII) (1:1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 57 publications
0
27
2
Order By: Relevance
“…A previous study showed that fish oil emulsions were significantly protected against lipolysis in the upper GI tract when stabilized by a heated matrix of protein, sugar and modified resistant starch (Patten, Augustin, Sanguansri, Head, & Abeywardena, 2009). This apparent discrepancy may be related to some notable differences between the studies.…”
Section: Bioactive Distribution In the Lumenmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study showed that fish oil emulsions were significantly protected against lipolysis in the upper GI tract when stabilized by a heated matrix of protein, sugar and modified resistant starch (Patten, Augustin, Sanguansri, Head, & Abeywardena, 2009). This apparent discrepancy may be related to some notable differences between the studies.…”
Section: Bioactive Distribution In the Lumenmentioning
confidence: 99%
“…In the present study a mixture of fish oil, tributyrin and resveratrol was used in the microencapsulated formulation, the rats were fasted for 9.5-14.5 h prior to dosing and were not fed after dosing (except in the case of the 24 h time point group where food was re-introduced at 8.5-10.5 h after dosing to avoid unacceptably prolonged fasting) and the unencapsulated bioactive mixture was administered in water (after vigorous vortexing to disperse the oil) prior to gavaging. However, in the previous study (Patten et al, 2009) there was only fish oil in the microencapsulated preparation, the rats were fasted for 24 h prior to dosing, rats were allowed food after dosing and the unencapsulated fish oil was gavaged as neat oil. The presence of food in the stomach at the time of gavaging appears to afford more protection to the encapsulated bioactives.…”
Section: Bioactive Distribution In the Lumenmentioning
confidence: 99%
See 1 more Smart Citation
“…This knowledge is being used by the pharmaceutical industry to develop lipid-based delivery systems that deliver drugs to specific locations within the GI tract (Porter & Wasan, 2008;Pouton, 2006). Similar systems are now being developed by the food industry to encapsulate, protect and deliver bioactive food components (McClements, Decker, Park, & Weiss, 2007;McClements et al, 2009;Patten, Augustin, Sanguansri, Head, & Abeywardena, 2009;Singh et al, 2009). Many of these delivery systems are being designed to modulate the digestion and release of bioactive food components within the GI tract.…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro digestion has been carried out in two phases: first, the encapsulated oil has been exposed to simulated gastric fluid (SGF) containing pepsin and sodium chloride at low pH value (Chung et al 2011), and second, an intestinal digestion was simulated by exposing gastric digestion elements to a simulated intestinal fluid (SIF) (Patten et al 2009). …”
Section: Microencapsulation Efficiencymentioning
confidence: 99%